Peran Teknologi Informasi Dalam Meningkatkan Minat Berwirausaha Ibu-Ibu PKK Perumahan Taman Jatisari Permai Bekasi - Srisulistiowati, Dwi Budi; Ramdhania, Khairunnisa Fadhilla; Setiawati, Siti; Rejeki, Sri (Journal Of Computer Science Contributions (JUCOSCO), 2021)
This paper describes about entrepreneurial activities that carried out by woman in Perumahan Jatisari, Bekasi. The concept of economic activity that is integrated with advances in information technology is one of the solutions that can support employment issues and simultaneously support the growth and prosperity of a nation's economy. Entrepreneurship online can be accepted as an alternative way to develop entrepreneurs in Indonesia. The form of buying and selling via the internet is known as e-commerce, and Indonesia has considerable opportunities in the online market. This era provides a large scope for organizing activities in new, innovative, transparent, and accurate so that information processing will be faster and easier. As a developing country, Indonesia continues to improve its network infrastructure by following various developments in information technology which will lead to an era in which the use of the internet has begun to become a daily necessity for all activities. Towards a digital economy marked by the growing development of business or trade transactions that utilize online media.